Study on the correlation between PPARγ, Aβ1-42, miR-155 and the occurrence and development of diabetes - Zhiping, Lv; Chunli, Liu; Shanna, Zhao (Cellular and Molecular Biology, 2022)
The objective of this research was to study the correlation between PPARγ, Aβ1-42, miR-155 and the occurrence and development of diabetes. For this purpose, 52 patients with diabetes who were hospitalized from September 2019 to May 2021 were selected as the research objects. They were grouped according to the severity of the disease, which was pre-diabetes (n=16), mild (n=25), and moderate (n=16). =11), another 20 healthy subjects were taken as the control group, and the levels of PPARγ, Aβ1-42, miR-155 in each group were measured, and the correlation between changes in the levels of various indicators and the occurrence and development of diabetes was explored. Results showed that comparison of age, gender, course of disease, BMI, living habits, comorbidities, and high-density lipoprotein among the groups of diabetic patients (P>0.05); the levels of total cholesterol, triglycerides and low-density cholesterol decreased with the development of diabetes (P<0.05) ); Compared with the healthy group, the levels of PPARγ and miR-155 were significantly reduced, and the levels of Aβ1-42 were significantly increased (P<0.05); compared with the prediabetes, the levels of mild and moderate PPARγ and miR-155 showed a downward trend, and Aβ1 -42 level showed an upward trend (P<0.05); PPARγ and miR-155 levels were negatively correlated with pre-diabetes, mild, and moderate; Aβ1-42 was positively correlated with pre-diabetes, mild, and moderate (P<0.05) ; PPARγ, Aβ1-42, miR-155 levels can effectively predict the occurrence and development of diabetes, and the sensitivity, specificity and accuracy of the detection of diabetes by various indicators, positive predictive value and negative predictive value are significantly higher. It is concluded that PPARγ, Aβ1-42, miR-155 are closely related to the occurrence and development of diabetes, and there are many influencing factors of diabetes. Clinical intervention measures can be taken according to specific conditions.